THE DEVELOPMENT OF REGIONAL EXPORT POTENTIAL - М. Karimbergenova; А. Nurgaliyeva; G.Kerimbek; S. Bespalyy; L.Moldashbayeva (Academic Journal of Physical and Chemical Sciences, 2019)
The paper presents general characteristics of Pavlodar region export potential and economic estimation of the use of Pavlodar region industrial productions export potential. It proves modern problems for the development of Pavlodar region industrial enterprises export potential. Every indicator is given according to the data from Agency of statistics of the Republic of Kazakhstan. Questions of rise in export potential at regional enterprises, formulation of a set of organizational and economic decisions that lead to the growth of export possibilities of the particular industrial productions using existing advantages, are important and timely. They help to solve an important economic task, such as growth of regional competitiveness and, as a result the whole national economy on world markets contributing to the balanced social development and decreasing social and economic tension in the region that demands an appropriate search of scientific approaches. Export potential in basic industries becomes an important stabilizing factor in conditions of economic development in regions, and it is also a basic source of foreign exchange into a regional budget. It is concluded that low level of innovative activity on industrial enterprises directly affects the level of export potential use both now and in the nearest future.